Effect of Al2O3 support on the activation parameters of the C–C bond catalytic cleavage in propanoic acid - R. S. Shamsiev; I. E. Sokolov; V. R. Flid (Тонкие химические технологии)
The effect of support on the activation parameters of C-C bond cleavage in a propanoic acid molecule was studied with DFT-PBE approach using the model of Pd9 cluster supported on (Al2O3)4 and (Al2O3)4(OH)2. Free activation energy is higher for Pd9/Al8O12 and Pd9/Al8O12(OH)2 (135-146 kJ∙mol-1 ) comparing to that of isolated Pd9 clusters (115-125 kJ∙mol-1 ). The effect of support is stronger (up to 31 kJ∙mol-1 ) for those structures, where the distance between Al8O12 and reactive palladium atoms is shorter. The energy of interaction between Pd9 and “dry” alumina compared to hydroxylated one (Al2O3)4(OH)2 is about two times less: 253-351 and 560-579 kJ∙mol-1 , respectively. The difference in energies is related to dependence of the energy of optimized structures on initial Pd9 location above alumina support. Despite that, activation parameters (Δ≠ G623) of C-C cleavage step differ slightly for (Al2O3)4 and (Al2O3)4(OH)2, from 1.3 to 5.6 kJ∙mol-1 . For all the models considered a carbon-carbon bond cleavage in a molecule of propanoic acid occurs as a threecentered interaction, viz. with participation of single Pd atom